2008
DOI: 10.1111/j.1365-2559.2008.02966.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathological, clinical and prognostic characteristics of breast cancer in Central Sudan versus Northern Italy: implications for breast cancer in Africa

Abstract: The differences between the Sudanese and Italian breast cancer series reflect stage at diagnosis rather than intrinsic biological characteristics. This may have relevant implications for breast cancer prevention and treatment in Africa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
81
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(109 citation statements)
references
References 52 publications
(195 reference statements)
22
81
4
Order By: Relevance
“…Compared with the Italian patients, the Sudanese patients were younger and their tumors were larger, more advanced in stage, higher in grade and more frequently positive for nodal metastases. Estrogen receptor (ER) expression varied between the two series, but no signiicant diferences were found for PgR, combined hormone receptors, Her-2/neu, CK5/6, CK17, combined basal CK status or breast cancer subtypes [33]. The study concluded that the diferences between the Sudanese and the Italian breast cancer series relected stage at diagnosis rather than intrinsic biological characteristics [33].…”
Section: Major Clinicopathological Features Of Breast Cancer In Sudanmentioning
confidence: 92%
See 2 more Smart Citations
“…Compared with the Italian patients, the Sudanese patients were younger and their tumors were larger, more advanced in stage, higher in grade and more frequently positive for nodal metastases. Estrogen receptor (ER) expression varied between the two series, but no signiicant diferences were found for PgR, combined hormone receptors, Her-2/neu, CK5/6, CK17, combined basal CK status or breast cancer subtypes [33]. The study concluded that the diferences between the Sudanese and the Italian breast cancer series relected stage at diagnosis rather than intrinsic biological characteristics [33].…”
Section: Major Clinicopathological Features Of Breast Cancer In Sudanmentioning
confidence: 92%
“…In limited resource countries, breast cancer is typically characterized by a relatively advanced stage at presentation [33,[36][37][38][39][40]. Data from National Cancer Institute, University of Gezira (NCI-UG) conirm that the patients with breast cancer present in small proportion with localized disease and in large proportion with regionally difuse and metastatic disease, as shown in Table 1.…”
Section: Major Clinicopathological Features Of Breast Cancer In Sudanmentioning
confidence: 99%
See 1 more Smart Citation
“…3,15,16 This shows that there is a difference in mean age of patients of breast carcinoma in developed and the developing nation. In the present study, maximum no.…”
Section: Discussionmentioning
confidence: 99%
“…Building Sustainable Capacity for Disease Diagnosis in Sub-Saharan Africa: Case Studies of Cooperation in Diagnostic Pathology 257 good quality research, and training programs (Dessein et al 1999;Mohamed-Ali et al 1999;Abel et al 2000;Pascal et al 2000;Henri et al 2002;Chevillard et al 2003;Dessein et al 2004;Alsheikh et al 2006;Awadelkarim et al 2007;Abuidris et al 2008a;Abuidris et al 2008b;Abuidris et al 2008c;Awadelkarim et al 2008;Dessein et al 2009;Faggad et al 2009a;Faggad et al 2009b;Rahoud et al 2009;Tofanelli et al 2009;Awadelkarim et al 2010a;Awadelkarim et al 2010b;Elgaili et al 2010;Elwali et al 2010;Ali et al 2011;Awadelkarim et al 2011). Its Nuclear Medicine, Oncology, Molecular Biology, Medical Physics and Engineering, Diagnostic Imaging and Medical Laboratories Departments make NCI-UG the only cancer institute outside the capital Khartoum (Figure 9).…”
Section: Wwwintechopencommentioning
confidence: 99%